Does mental health practice benefit from procedural justice theory? A critical analysis on the opportunities and pitfalls of procedural justice to address coercion and human rights issues in psychiatry - Lessard-Deschênes, Clara; Pariseau-Legault, Pierre; Goulet, Marie-Hélène (Aporia)

(untitled) (University of Ottawa, 2024)
The theory of procedural justice, derived from social psychology, is employed in numerous fields of study concerned with the quality of interactions involving individuals in positions of authority. Although this theory is increasingly cited for its potential to promote approaches aimed at mitigating the effects of psychiatric coercion and better respecting individuals' rights, empirical literature provides limited insights into how procedural justice could be translated into practice. It is important, therefore, to examine the theoretical and practical implications of such an orientation. Based on a critical analysis of existing literature, this article will discuss the potential contributions and limitations of procedural justice applied in the field of mental health and psychiatric nursing. Procedural justice has limitations regarding solutions for human rights violations in psychiatry. It nonetheless allows a focus on the quality of interactions with individuals in coercive contexts, in addition to considering the social and identity-related implications of psychiatric coercion.